Hydration behavior of an experimental tricalcium silicate/tetracalcium phosphate bio-cement in Streptococcus thermophiles bacterial solution in comparison with distilled water used as a root canal furcation perforation repair material - Radwan, M. M. (2023)
Setting time and micro-hardness The setting time of the synthesized material was carried out according to “Setting time” section by using the workable paste prepared at a water/powder ratio of 0.22 ml/g. Mixing the dry material powder with distilled water in such proportion results in a workable paste by which final setting time is determined. The average final setting time was found to be 22 min at 37 °C. In this investigation, the micro-hardness was considered as a mechanical property for the influence of Streptococcus thermophilus microbe incubated in nutrient broth media (NB) on the hydraulic behavior of the hardened pastes at the different curing periods in comparison with those cured in distilled water. Figure 3 represents the measured hardness values of pastes cured under DW and NB media for different curing ages. Figure 3 reveals that the hardness values of the samples cured under distilled water increase from 1 to 14 days.